Epistemic entrenchment-based multiple contractions - Fermé, Eduardo (2013)
In this article we present a new class of multiple contraction functions—the epistemic entrenchment-based multiple contractions—which are a generalization of the epistemic entrenchment-based contractions (Gardenfors, 1988; G ¨ ardenfors & Makinson, 1988) to the case of ¨ contractions by (possibly nonsingleton) sets of sentences and provide an axiomatic characterization for that class of functions. Moreover, we show that the class of epistemic entrenchment-based multi ple contractions coincides with the class of system of spheres-based multiple contractions introduced in Ferme & Reis (2012).